PENINGKATAN KAPASITAS PELAKU WISATA PETIK BUAH SEBAGAI UPAYA PENGEMBANGAN DESA WISATA TULUNGREJO, KECAMATAN BUMIAJI, KOTA BATU - Tsalasati, Shinta; Fibrianingtyas, Alia; Laili, Fitrotul (Indonesian Collaboration Journal of Community Services (ICJCS), 2025)
Indonesia has many villages with the potential to become tourism villages, one of which is Tulungrejo Village in Bumiaji District, Batu City. This village has the largest apple orchard covering approximately 900 hectares and has also developed strawberry-picking agrotourism. Such potential highlights the need to strengthen the capacity of tourism actors, particularly in tourism services and interpretation. The empowerment program aims to: (1) identify the potentials and challenges of fruit-picking tourism; and (2) enhance the cognitive and affective capacity of tourism actors through socialization. Social mapping was conducted using observation, interviews, focus group discussions (FGD), and ranking methods. The results show promising potentials such as an active community, high enthusiasm, and strong tourism appeal, while the challenges include a lack of collaboration, limited tourism management skills, and inconsistency in standard operating procedures (SOP). The program involved 13 participants and was carried out using a mezzo-level approach through socialization and practical activities. Pre-test and post-test evaluations indicated an increase of 17% in cognitive aspects and 9% in affective aspects, but the results did not meet the minimum target of 60%, suggesting that the program has not been fully successful. Nevertheless, the applied method proved to be quite effective and may serve as a foundation for future program development. Recommendations include encouraging tourism actors to establish communication with POKDARWIS and Karang Taruna, and to prepare for professional certification; the village government is encouraged to provide continuous mentoring, training, and infrastructure support; and future facilitators are advised to strengthen material on stakeholder roles, adopt participatory approaches, and adjust evaluation indicators to match participant backgrounds.